Followers' personality, transformational leadership and performance. Issue 1 (9th March 2015) - Soane, Emma; Butler, Christina; Stanton, Emma
Abstract : Purpose: – Effective leadership is important to performance in both organisational and sporting arenas. The authors theorised that follower personality would influence perceptions of leadership, and that perceived effective leadership would be associated with performance. The authors drew on Social Identity Theory (Tajfel and Turner, 1986), Transformational Leadership and personality theory to develop a research model designed to assess leadership effectiveness and performance. The purpose of this paper is to test the research model in a sporting context. Design/methodology/approach: – The context of the research was a round the world sailing race, a ten-month competitive circumnavigation with ten identical boats. Quantitative data were gathered concerning participants' personality, their perceptions of transformational leadership and boat performance. Qualitative data on transformational leadership and leadership effectiveness were gathered from a subsample of crew members. Findings: – Results showed that transformational leadership was associated with leadership effectiveness and performance. Personality influenced perceptions of leadership and, for moderate performing boats, there were associations between perceptions of leadership and performance. Research limitations/implications: – The data have implications for the extension of transformational leadership theory. Further consideration of follower personality could enhance leadership effectiveness. A limitation is the relatively small scale of the study. Practical implications: – The main implication is that leaders should take follower personality into account, and adapt their leadership style accordingly. Doing so has consequences for performance. Originality/value: – This novel study examined personality, leadership, and performance and has implications for enhancing leadership and performance in sports and business.